TORQUE MEASUREMENT IN WORM AGLOMERATION MACHINE - Marian DUDZIAK; Ireneusz MALUJDA; Krzysztof TALAŚKA (Scientific Journal of Silesian University of Technology. Series Transport)
The paper presents the operating characteristics of the worm agglomeration machine. The paper indicates the need for continuous monitoring of the value of the torque due to the efficiency of the machine. An original structure of torque meter which is built in the standard drive system of briquetting machine was presented. A number of benefits arising from the application of the proposed solution were presented. Exemplary measurement results obtained by means of this torque meter were presented.